IMPLEMENTATION OF DIAGNOSTIC ASSESSMENT IN GRADE VI TEACHING AT THE RIGHT LEVEL APPROACH IN INDONESIAN LANGUAGE LESSONS IN ELEMENTARY SCHOOL - Asharif Suleman, Muh.; Idayanti, Zulfi (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2024)
This study aims to examine why teachers need to use diagnostic assessments of Indonesian language lessons in classes that implement the Teaching at the Right Level (TARL) approach. This study is a qualitative study with a case study approach. This study was conducted in class V (NUH) with 47 students. Data were obtained by collecting the results of diagnostic assessments of three different classes (up to medium, low) of Indonesian language lessons. The assessment was adapted from the book "Bahasa Indonesia: Anak-Anak Yang Ubah Dunia," published by KEMENDIKBUDRISTEK in 2022. The results of the study found that class VI, which was divided into three classes based on the results of the previous semester's report card scores and adjusted to the children's ability levels, showed significant differences between the level-up and low-level classes. 20 students were grouped in class NUH 1 (level up) and answered according to the instructions and directions of the questions with maximum scores. 15 students were grouped into NUH 2 (medium) class, 50% of students answered incorrectly, and 12 students were grouped into NUH 3 (low) class. Only 5 children followed the instructions and directions of the questions from the total of 12 children, plus it turned out that there were 2 students who needed reading assistance from the teacher. This study is expected to provide a strong reason that teachers are advised to apply diagnostic assessments before lessons to be used as a reference for providing stimulus or supporting media for learning, especially Indonesian language lessons.